‘Customary’ use of stick tools by chimpanzees in Bulindi, Uganda: update and analysis of digging techniques from behavioural observations - Matthew R. McLennan; Jacqueline Rohen; Zoe Satsias; Tom Sabiiti; John-Mary Baruzaliire; Marie Cibot (Revue de Primatologie)
Wild chimpanzees commonly use stick tools in foraging, often to harvest honey and other insect foods. Compared to other geographical regions, chimpanzees (Pan troglodytes schweinfurthii) in mid-western Uganda generally have small toolkits, with one long-term study group – the Sonso community in Budongo Forest – exhibiting no foraging stick use whatsoever. Twenty-five kilometres outside Budongo, the Bulindi community inhabits small forest fragments amidst farmland and villages. Earlier studies reported indirect evidence that these chimpanzees use sticks for digging out subterranean nests of stingless bees (Meliponini) for honey. This article updates the earlier findings on stick tool use at Bulindi using opportunistic direct observations made between June 2018 and March 2020. We first established that foraging stick tool use is ‘customary’ at Bulindi, i.e., occurring in most or all adult, subadult and juvenile individuals. The chimpanzees use stick tools in various foraging contexts, for example as probes to investigate branches or logs containing insect prey or products (e.g., Apis mellifera and Xylocopa sp. bee nests, and unidentified grubs or larvae), as well as for excavating Meliponini ground nests. Next, we analysed video recordings of tool-assisted digging involving six individuals and compared their behaviour with the highly complex techniques (‘actions’) performed by chimpanzees (P. t. troglodytes) in Loango, Gabon – the only site with available data on behavioural techniques used to excavate ground bee nests. While data from Bulindi are preliminary, most actions and grip types described from Loango are present in the Bulindi repertoires. Our observations further indicate high social tolerance in the context of tool-assisted digging in Bulindi, including instances of tool transfer among individuals. Overall, our study suggests close alignment between the techniques used to accomplish this complex tool-assisted task in Bulindi chimpanzees in East Africa and Loango chimpanzees in Central Africa, separated by 2,500 km. Anthropogenic impacts including forest loss, fragmentation, and degradation might reduce behavioural and ‘cultural’ diversity in chimpanzees through loss of opportunities for social transmission of behaviours. Even so, the Bulindi example demonstrates that complex stick tool use can occur in populations occupying highly modified habitats, while being seemingly absent in nearby continuous forest (i.e., Budongo Forest).